IN MEMORY OF LUCIANO CORTESOGNO (Ofioliti, 2005)
Luciano Cortesogno, Full Professor of Petrology and Petrography at the Science Faculty of Genoa University, died on the 23rd of May 2005 at the age of 64. For his wide-angle scientific interests, he represents one of the most complete figures in the national and international scientific scenario. More than 160 articles, co-authored with many Italian and foreign colleagues, 5 geological maps with notes, the collaboration to several CARG 1:50.000 maps, invitations as key-note speaker testify for an active and appreciated member of the Earth Science community.Since 1970, Luciano Cortesogno developed investigations addressed to primary, ocean floor and orogenic processes in the oceanic lithosphere. In those years, starting from extensive, accurate, interpretive field survey and mapping, through deep and exhaustive mineralogical, petrographic, petrologic analyses, achieving full-fitting geodynamic models, he contributed to the bases of Tethyan ophiolite geology. A distinctive character of Lucio was the capacity to collaborate and integrate the contribution from other disciplines: stratigraphy, structural geology, geochemistry, mineralogy, and to create robust friendships within the Ofioliti Working Group.Milestones of his scientific production on ophiolites are the articles on high- and low-grade ocean floor alteration in Apennine gabbros, on ophicalcite petrogenesis, on high-pressure metamorphisms (blueschists, eclogites), on the reconstruction of the genesis and evolution of the Northern Apennine oceanic lithosphere, on the Alps-Apennine boundary, on the orogenic evolution and metamorphism in the Ligurian Alps and in the Northern Apennine. The international resonance of his work called on the Ligurian ophiolites many foreign colleagues; the world-known Sestri-Voltaggio Zone, part of the Alps-Apennine boundary, was unraveled with the French geologist Daniel Haccard through a 15-years lasting work.In the meantime, his scientific interests also widened to petrogenesis in the continental crust of the Ligurian Pennidic terranes: Lower Palaeozoic stratigraphy and metamorphic evolution, Late Variscan volcanism, plutonism, stratigraphy, Triassic volcanism. His research, in a fruitful collaboration with Pavia colleagues and friends, firstly Mario Vanossi, was developed across many years of field and laboratory work, and resulted in an exhaustive reconstruction of an orogenized passive margin.In the 90ies he was invited to join some international projects on Albanian and Uralian ophiolites that he faced with the usual wide capacity and deep dedication. Moreover, the investigations on the continental Permian were extended throughout Southern Europe (Sardinia, Bulgaria, Southalpine, Provence) with the “volcanic” friend Bepi Cassinis, yielding a consistent and interdisciplinary picture of the Variscan late orogenic phases, and further insights in the Late Permian-Triassic anorogenic volcanic events.This high-level and huge scientific production has been coupled with a generous teaching activity to undergraduate and PhD students, openness to discussion and suggestions to younger researcher. Some of his former students are now full, associated professors and researchers in Genoa and Pavia Universities, or outstanding professional consultants.Who has been in the field or had discussed with him remembers “A nice person with a deep knowledge of geology as well as botany and fauna, and a good fellow in field meetings” and “C’était un collègue comme on les aime: compétent, attentif, discret, avec des connaissances sûres et sérieuses qu’il n’hésitait pas à partager. Il a laissé une empreinte profonde au Laboratoire de Gênes et sur la géologie des Alpes ligures.” “He was not only an excellent geologist but also a very good naturalist interested by many aspects of natural sciences, a very cultured and sympathetical collegue.”